2022
DOI: 10.1136/jitc-2021-003190
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of dendritic cell-based immunotherapy DCVAC/OvCa added to first-line chemotherapy (carboplatin plus paclitaxel) for epithelial ovarian cancer: a phase 2, open-label, multicenter, randomized trial

Abstract: BackgroundMost patients with epithelial ovarian cancer (EOC) relapse despite primary debulking surgery and chemotherapy (CT). Autologous dendritic cell immunotherapy (DCVAC) can present tumor antigens to elicit a durable immune response. We hypothesized that adding parallel or sequential DCVAC to CT stimulates antitumor immunity and improves clinical outcomes in patients with EOC. Based on the interim results of sequential DCVAC/OvCa administration and to accommodate the increased interest in maintenance treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…We recently published the results of three independent open-label, randomized Phase I/II, II and III clinical studies that compared the efficacy of an autologous DC-based vaccine (DCVAC) delivered in the context of standard of care chemotherapy (SOC) versus SOC alone in patients with advanced non-small cell lung carcinoma (NSCLC; SLU01, NCT02470468), 21 epithelial ovarian cancer (EOC; SOV01, NCT02107937), 22 , 23 or metastatic castration-resistant prostate cancer (mCRPC; SP005, NCT02111577). 24 In these settings, DCVAC was well tolerated and significantly extended the progression-free survival (PFS) and overall survival (OS) of EOC or NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently published the results of three independent open-label, randomized Phase I/II, II and III clinical studies that compared the efficacy of an autologous DC-based vaccine (DCVAC) delivered in the context of standard of care chemotherapy (SOC) versus SOC alone in patients with advanced non-small cell lung carcinoma (NSCLC; SLU01, NCT02470468), 21 epithelial ovarian cancer (EOC; SOV01, NCT02107937), 22 , 23 or metastatic castration-resistant prostate cancer (mCRPC; SP005, NCT02111577). 24 In these settings, DCVAC was well tolerated and significantly extended the progression-free survival (PFS) and overall survival (OS) of EOC or NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
“… 24 In these settings, DCVAC was well tolerated and significantly extended the progression-free survival (PFS) and overall survival (OS) of EOC or NSCLC patients. 21 , 22 In mCRPC patients, DCVAC combined with SOC and continued as maintenance treatment showed a favorable safety profile but did not extend OS. 24 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence demonstrates that both the type and extent of immune infiltration correlate with OV patients' outcome [ 23 ]. In a recent clinical trial, the addition of dendritic cell-based immunotherapy to the first-line chemotherapy (carboplatin plus paclitaxel) significantly improved progression-free survival of epithelial OV patients [ 24 ]. Resolution of immune cells in the exudate of OV patients revealed that higher proportions of B cells and NK cells corresponded to worse patient survival, with the coincidence of higher B cells in FIGO stage IV patients than in stage III [ 25 ].…”
Section: Introductionmentioning
confidence: 99%